Development of internet marketing model in banking industry based on big data technologies - Vasiljević, Dragana; Despotović-Zrakić, Marijana (E-business technologies conference proceedings, 2021)
The subject of this paper is use big data technologies in banking sector. The key issue, which has been presented in the paper, is the research and development of internet marketing models that are based on clients’ movements on the bank’s digital portals. The goal of the research done is to improve the communication between the bank and its clients and to contribute to portraying particularities in behavior, interests and wishes of clients by developing and applying new models of internet marketing. The aim of the research is to increase the quality and efficiency of marketing and sales strategies of the Bank in order to integrate relevant processes such as data collection and analysis, CRM banking system, with the intention of improving the design and usability of the system when posting content on bank portals.